2003
DOI: 10.1118/1.1558675
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the predictability of diaphragm motion during respiration with a noninvasive external marker

Abstract: The aim of this work was to quantify the ability to predict intrafraction diaphragm motion from an external respiration signal during a course of radiotherapy. The data obtained included diaphragm motion traces from 63 fluoroscopic lung procedures for 5 patients, acquired simultaneously with respiratory motion signals (an infrared camera-based system was used to track abdominal wall motion). During these sessions, the patients were asked to breathe either (i) without instruction, (ii) with audio prompting, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
240
2
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(256 citation statements)
references
References 48 publications
6
240
2
8
Order By: Relevance
“…This suggests that VBF would need to be implemented throughout the entire radiation therapy workflow. Our findings were contrary to those obtained by Vedam et al, (25) who studied five lung cancer patients with fluoroscopy and found that diaphragm motion was comparable with and without VBF. Another study showed VBF reduced respiratory amplitude by up to 40% (26) .…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that VBF would need to be implemented throughout the entire radiation therapy workflow. Our findings were contrary to those obtained by Vedam et al, (25) who studied five lung cancer patients with fluoroscopy and found that diaphragm motion was comparable with and without VBF. Another study showed VBF reduced respiratory amplitude by up to 40% (26) .…”
Section: Discussioncontrasting
confidence: 99%
“…Note that the development of our framework is independent of the data used, be it data collected with an external marker placed on the abdomen during breathing or internal tumour motion data obtained from a fluoroscopic marker. Ideally, in the optimization, a treatment planner would use data describing actual tumour motion induced by breathing, or external data plus the appropriate parameters to correlate internal motion to the external marker (Vedam et al 2003, Gierga et al 2005, Tsunashima et al 2004.…”
Section: From Patient Data To a Model Of Uncertaintymentioning
confidence: 99%
“…1) from the abdominal marker with the largest respiratory amplitude. The NPM component along the Y axis of abdominal markers mostly reflects the trend changes in respiration (motion of the diaphragm [13]) as physical motion of the patient downwards in the vertical direction is restricted due to the bed and it is unlikely the patients would sustain a vertical motion upwards off the bed. The following parameters are used to quantify respiratory motion:…”
Section: Respiratory Motion Parametersmentioning
confidence: 99%